Serum and Urine Neutrophil Gelatinase-Associated Lipocalin Levels Measured at Admission Predict Progression to Chronic Kidney Disease in Sepsis-Associated Acute Kidney Injury Patients. (18th August 2020) - Tuan, Pham Ngoc Huy; Quyen, Dao Bui Quy; Van Khoa, Huynh; Loc, Nguyen Duc; Van My, Pham; Dung, Nguyen Huu; Toan, Nguyen Duy; Quyet, Do; Thang, Le Viet
Abstract : Background . To evaluate the ratio of acute kidney injury (AKI) to chronic kidney disease (CKD) in sepsis-associated acute kidney injury (SA-AKI) patients of the intensive care unit (ICU) and predictive value of neutrophil gelatinase-associated lipocalin (NGAL) measured at the admission time in the progression of AKI to CKD. Methods . A study of 121 consecutive adult patients admitted to the intensive care unit (ICU) diagnosed as SA-AKI. AKI and CKD were defined based on Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Glomerular filtration rate (GFR) was calculated by the CKD-EPI formula. Serum and urine NGAL was measured using the BioVendor Human Lipocalin-2/NGAL ELISA with a blood sample taken at hospital admission time. Results . The ratio of AKI to CKD in SA-AKI patients was 22.3%. Mean concentration of serum and urine NGAL in AKI to the CKD group was 790.99 ng/ml and 885.72 ng/ml, higher significantly than those of recovery patients (351.86 ng/ml and 264.68 ng/ml), p < 0.001 . eGFR, both serum and urine NGAL had a predictive value for AKI to CKD (eGFR: AUC = 0.857, Se = 74.1 %, Spe = 92.6 %, p < 0.001 . Serum NGAL: AUC = 0.868, Se = 77.8 %, Spe = 91.5 % . Urine NGAL: AUC = 0.869, Se = 77.8 %, Spe = 92.6 %, p < 0.001 . Conclusion . Serum and urine NGAL, measuring at hospital admission time, were good prognostic biomarkers of AKI to CKD in SA-AKI patients.